The Nostalgia of the Light and the Memory of the Stars:: Patricio Guzmán's cinema - Lessa Filho, Ricardo (2018)
The images of the work of Patricio Guzmán have no more noble and concrete destiny than to rescue the memory suppressed by the Chilean dictatorship of Augusto Pinochet. His images give us a lesson of history and humanity. From the analysis of fragments of the Chilean director's films, this essay intends to examine the idea of rescue and embodiment of a physical and affective memory, starting from the possibilities opened by the survival of theimages recorded by Guzmán's films, that struggles to prove the Pinochet's crimes, and to honor the identity of the dead in that period.